THE INFLUENCE OF THE AGRICULTURAL SECTOR ON ECONOMIC GROWTH IN THE PERSPECTIVE OF ISLAMIC ECONOMICS (NORTHERN ACEH DISTRICT) - Mutiara Shifa; Tio Devilishanti; Dian Apriani; Muhammad Natsir; Mawaddah Putri Arisma Siregar (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study is to determine the effect of the agricultural sector and harvest area on economic growth and how economic growth is in the perspective of Islamic economics. The data used are time series from 1998-2020 published by BPS. The results showed that the agricultural sector and harvest area had a negative and significant effect on economic growth in North Aceh Regency. Economic growth in Islam does not only focus on the welfare of the world but includes welfare in the world and the hereafter.